The relationship between human resource practices and employees’ commitment to change in Malaysia Higher Education - Lo, May Chiun; Mung, Ling Voon; Ramayah, T. (The Global Studies Jounal, 2010)
Extensive researches are available in the organizational behaviour literature investigating the process of Human Resources (HR) practices and commitment to change. But the two constructs—HR practices and commitment to change seems to have been examined almost independently. This is particularly true in the Malaysian context as researchers have speculated that HR practices may have an impact upon subordinates’ perceptions of supervisory power. This study explores the relationship between HR practices and commitment to change in selected public universities in Malaysia. It focuses on how HR practices have affected the level of employee’s commitment to change towards the employing organization. Five dimensions of HR practices were used in this study, namely participation and involvement, training and development, performance appraisal, incentive and compensation. Two hundred and seventy eight academic staff of selected public universities in Malaysia voluntarily participated in this study. Implications of the findings were discussed further.